School Violence and Mental Health in Chilean Digital Media Post-COVID-19: An Analysis from the Theories of Collective Subjectivity - Rodríguez-Pastene Vicencio, Fabiana Carola; Castro Carrasco, Pablo; Cuadra Martínez, David; Sorza Molina, Sara (Revista Española de Comunicación en Salud, 2025)
Introduction: According to the National Institute for Human Rights, in the first half of 2022, following the end of the Covid-19 pandemic, 1,700 more reports of school violence were recorded in the first half of 2022 compared to the previous two years and media coverage of violent crime has increased significantly. Objectives: to identify -under the model of Subjective Theories (ST)- those aspects present in the media discourse related to the causes, intervening conditions and strategies for dealing with school violence after the return to face-to-face attendance in Chilean educational establishments. This violence, exacerbated in the post-pandemic context, has a negative impact on the mental health of students, which makes it a relevant phenomenon for public health policies. Methodology: a comparative content analysis of the publications of SoyChile.cl and El Mostrador.cl during the last month of classes in 2022 was carried out. Results: both media explained the phenomenon as ‘a structural problem’, distancing diagnosis and treatment from the actors directly involved. Conclusion: school violence is considered an unavoidable and unapproachable reality, factors that exempt caregivers, teachers, principals, authorities and students who could eventually take an active part in the prevention or solution of the phenomenon from responsibility.
Keywords: school violence; school coexistence; press; subjective theories